War‐related trauma linked to increased sustained attention to threat in children. Issue 4 (11th February 2022) - Michalek, Julia; Lisi, Matteo; Binetti, Nicola; Ozkaya, Sumeyye; Hadfield, Kristin; Dajani, Rana; Mareschal, Isabelle
Abstract: Experiences of war and displacement can have profound effects on children's affective development and mental health, although the mechanism(s) underlying these effects remain unknown. This study investigated the link between early adversity and attention to affective stimuli using a free‐viewing eye‐tracking paradigm with Syrian refugee ( n = 31, M age = 9.55, 12 female) and Jordanian non‐refugee ( n = 55, M age = 9.98, 30 female) children living in Jordan (March 2020). Questionnaires assessed PTSD, anxiety/depression, insecurity, distress, and trauma. Refugee children showed greater initial avoidance of angry and happy faces compared to non‐refugee children, and higher trauma exposure was linked to increased sustained attention to angry stimuli. These findings suggest that war‐related trauma may have differential effects on the early and later stages of affective processing in refugee children.